2021
DOI: 10.7759/cureus.13862
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic Management of Endobronchial Atypical Carcinoid With Argon Plasma Coagulation and Laser: A Rare Case With Literature Review

Abstract: Atypical carcinoid belongs to a spectrum of neuroendocrine tumors that can present as central airway obstruction. We treated a 58-year-old female who presented with recurrent pneumonia. Flexible bronchoscopy showed complete obstruction of the tumor in the right lower lobe. The tumor was excised by electrocautery snare followed by laser and argon plasma coagulation (APC). Endobronchial biopsy showed atypical carcinoid with lymph node metastasis. Succeeding bronchoscopic management, the patient’s symptoms improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It is difficult, clinically, to discern whether there is a residual tumor at the resection margin during endobronchial surgery. Previous studies have reported that additional laser ablation at the tumor bed was effective in preventing tumor recurrence [ 25 , 26 , 27 ]. Therefore, we performed laser and Argon Plasma Coagulation (APC) therapy after resection.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult, clinically, to discern whether there is a residual tumor at the resection margin during endobronchial surgery. Previous studies have reported that additional laser ablation at the tumor bed was effective in preventing tumor recurrence [ 25 , 26 , 27 ]. Therefore, we performed laser and Argon Plasma Coagulation (APC) therapy after resection.…”
Section: Discussionmentioning
confidence: 99%